Methodological Trends in Classical and Modern Arabic Literary Criticism: A Comparative Study on the Evolution of Arabic Literary Criticism - Ruly Syaepul Azhar; Tiana Nur Azizah Suparman; Ahmad Kholil Al-Maghfur; Rizzaldy Satria Wiwaha (EL-IBTIKAR: Jurnal Pendidikan Bahasa Arab, 2025)
Arabic literary criticism is a vital component of the Arab intellectual tradition, evolving alongside the development of Arabic literature across various historical periods. This article aims to compare the characteristics and approaches of classical and modern Arabic literary criticism by examining their respective features, methods, and underlying principles. This research employs a qualitative method with a comparative study approach, analyzing relevant literature including books, journals, and scholarly articles. The data is processed through narrative and descriptive analysis involving data reduction, presentation, and verification. The findings indicate that classical Arabic criticism tends to be intuitive and normative, focusing on linguistic accuracy, poetic structure, and aesthetic appreciation, rooted in oral tradition and Arabic rhetoric. In contrast, modern Arabic criticism has grown into a more scientific and interdisciplinary practice, influenced by Western theories such as structuralism, psychoanalysis, and postcolonialism, with a contextual emphasis on meaning and ideology within literary texts. This study shows that the difference in critical paradigms reflects not only a shift in time periods but also broader cultural and intellectual transformations, making Arabic literary criticism a dynamic and ever-evolving field